Genetic diversity of ‘Candidatus Liberibacter asiaticus’ in Brazil analyzed in different geographic regions and citrus varieties - de Paula, Larissa Bonevaes [UNESP]; Lin, Hong; Stuchi, Eduardo Sanches; Francisco, Carolina Sardinha; Safady, Nágela Gomes; Coletta-Filho, Helvécio Della (Springer Nature, 2019)
The bacterium ‘Candidatus Liberibacter asiaticus’ - CLas, the agent associated with citrus huanglongbing disease was first reported in Sao Paulo State in 2004 and has spread throughout the citrus-growing regions of Sao Paulo and further to the states of Minas Gerais and Parana. However, little information is available regarding the genetic diversity of CLas since its introduction. Understanding the genetic diversity of this bacterium is important for tracing migration routes and for identifying evolutionary selection forces that may affect the genetic diversity of this pathogen. Total DNA from 199 HLB-diseased citrus species trees was sampled from geographic regions in Sao Paulo, Parana and Minas Gerais states and the CLas isolates were genotyped by simple sequence DNA repeats (SSR). Nei’s genetic diversity index was observed to be low in all populations (H Nei = 0.11–0.26). Wright’s fixation index (F ST ), which measures population genetic differentiation, did not differ significantly between CLas populations from Sao Paulo State and from Minas Gerais, but significant values (F ST = 0.118–0.191) of the Parana CLas population distinguish it from the others. Interestingly, higher values (F ST = 0.275–0.445) were observed for the CLas populations obtained from different citrus species compared to sweet orange, suggesting that the citrus genotypes could be driven the genetic diversity of CLas. Clustering analysis supports the F ST results that split the CLas samples into three genetically distinct populations. These results indicate that genetically homogeneous populations of CLas infect sweet orange plants in various regions of Sao Paulo State and Minas Gerais, but not Parana, suggesting that different introduction events may have occurred for the Sao Paulo and Parana states.
Keywords: Citrus pathogen; Genetic diversity; Greening; SSR